Specialized Genetic Algorithm of Chu-Beasley Applied to the Distribution System Reconfiguration Problem Considering Several Demand Scenarios - Souza, Simone S. F. [UNESP]; Romero, Ruben [UNESP]; Pereira, Jorge; Saraiva, J. T.; IEEE (Ieee, 2015)
This paper describes the application of the specialized genetic algorithm of Chu-Beasley to solve the Distribution System Reconfiguration, DSR, problem considering different demand scenarios. This algorithm is an approach inspired in the natural selection and evolution of species. The reconfiguration problem of distribution networks taking into account different demand scenarios aims at identifying the most adequate radial topology of a distribution system assuming that this topology is used for all demand scenarios under study. This search is driven by the minimization of the cost of energy losses in the network along a full operation year. The performance of the algorithm is evaluated considering test systems having 33, 70, 84 and 136 buses and a real system with 417 buses. The obtained results confirm the robustness and efficiency of the developed approach and its potential to be used in distribution control centers.
Keywords: Distribution System Reconfiguration; Demand scenarios; Specialized Genetic Algorithm of Chu-Beasley; Mixed-Integer Nonlinear Programming Problem